(untitled) (Revista LIDER, 2017)
The work presented here, is intended to analyze fiscal policy in Mexico. This analysis aims to be the theoretical and conceptual foundation which, as a core structure, will serve as a basis for research on fiscal policy in Mexico. Although the situation may seem very complex, the research starts from the assumption that the application of the current federal tax policy has implications for economic development in general. Empirical studies on the topic, as well as the model of fiscal policy are included.